Assessment of Free and Total Cyanide Levels in the Water Environment of Shatt Al-Arab - Zuhair Ali Abdulnabi (Universitas Gadjah Mada, 2020)
The concentration of free and total cyanide in waters was measured by using the colorimetric method through complex formation with pyridine-barbituric acid at the wavelength of 578 nm. Ten stations were selected from water surfaces in the south of Iraq. The samples were distributed among two stations, one was on Euphrates River and the other was on Tigris River (before their confluence and formatting of Shatt Al-Arab) and selected seven stations along Shatt Al-Arab River. All the samples were collected from surface water at depth of 10–15 cm and their pH was adjusted to 12 by using sodium hydroxide. The results showed the highest concentration of free cyanide (0.254 mg/L) in station W7 and the lowest concentration in stations W2, W9 and W10, while the highest and lowest concentration of total cyanide (9.962, 0.207 mg/L) were recorded in station W7 and W1 respectively. The standard deviation of all sites (n = 3) of free and total cyanide was calculated and showed 0.007–0.048 and 0.001–0.042 ranges respectively. Furthermore, some of the physico-chemical properties of water were recorded in these stations.